Pengujian Aplikasi Sistem Informasi Absensi Karyawan PT Prakarsa Mitra Andalan Menggunakan Metode Black Box - Sri Mulyati; Irpan Kusyadi; Alex Saputra; Henriansyah Hidayat; Sulthon Aulia Azis Akbar (Program Studi Teknik Informatika Universitas Pamulang, 2022)
Technological developments that gave birth to many quality software products. Quality software is software that has gone through testing. In software testing there are several things that must be tested, namely the software must be in accordance with what the user wants or needs, the software must work well when used so that there are no errors, the software must have a good response time when run. Software must be a cost and time efficiency solution. In software testing, one of the methods used is by using the blackbox method. The blackbox method has its own technique, one of which is the equivalence partitioning technique. The equivalence partitioning technique is a technique of dividing several parts or partitions to check each part or partition by testing the software.